miR-376a Provokes Rectum Adenocarcinoma Via CTC1 Depletion-Induced Telomere Dysfunction - Liu, Yang; Zhao, Xiaotong; Wang, Bing; Liu, Zhijia; Zhang, Manman; Wang, Jinhan; Xu, Chang; Wang, Yan; Du, Liqing; Wang, Feng; Wang, Qin; Liu, Qiang (Frontiers in Cell and Developmental Biology, 2021)
CTC1 is a component of the mammalian CST (CTC1-STN1-TEN1) complex, which plays essential role in resolving replication problems to facilitate telomeric DNA and genomic DNA replication. We previously reported that the depletion of CTC1 lead to stalled replication fork restarting defects. Moreover, the mutation in CTC1 caused cancer-prone diseases including Coats plus (CP) or dyskeratosis congenita (DC). To better understand the CTC1 regulatory axis, the miRNAs targeting to CTC1 was predicted by the bioinformatics tool, and selected candidates were further confirmed by dual-luciferase reporter assay. Here, our current results revealed that miR-376a significantly reduced CTC1 expression at the transcription level, by recognizing CTC1 3’-UTR. In addition, the overexpression of miR-376a induced telomere replication defection and resulted in direct replicative telomere damage, which could be rescued by adding back of CTC1. Telomere shortening was also observed upon miR-376a treatment. Furthermore, for the clinical patient samples, the high expression of miR-376a was associated with the deregulation of CTC1 and a poor outcome for the rectum adenocarcinoma patients. Together, our results uncovered a novel role of miR-376a in provoking rectum adenocarcinoma progression via CTC1 downregulating induced telomere dysfunction.